Accounting Information Usage and Trading by Retail Investors: Evidence from Integrated Trading Platform - CHAU, JACKY (Journal of Accounting Research, 2025)
ABSTRACT This registered report investigates self‐directed retail investors' information choices and trading decisions on an integrated trading platform that provides timely and convenient access to accounting information. The analyses reveal that these investors access a mosaic of information, with a high proportion not firm‐specific. In accessing accounting disclosures, retail investors are more interested in media articles providing summaries or expert analyses than original filings. Retail trades on this integrated trading platform are more informed than another retail trading platform providing little information services while exhibiting no significant differences in informativeness compared with institutional trades using Bulge Bracket platforms. In particular, trade informativeness is more pronounced when there are accounting disclosures. The evidence suggests that self‐directed retail investors can benefit from a trading environment that provides rich and convenient access to a mosaic of information, particularly timely accounting disclosures.